Integrity checking of 1149.4 extensions to 1149.1 - Felgueiras, Carlos (2006)
The IEEE 1149.4 Standard for a Mixed-Signal (MS) Test Bus proposes an extension to the well-accepted IEEE 1149.1 boundary-scan test architecture, with the objective of facilitating interconnect, parametric and internal testing of MS circuits. An Analog Test Access Port (ATAP) comprising two pins called AT1 and AT2, and an internal analog bus (AB) comprising two lines (AB1, AB2), enable analog test stimulae and responses to be routed to any pin possessing an Analog Boundary Module (ABMs replace the IEEE 1149.1 test cells in the case of analog pins). A Test Bus Interface Circuit (TBIC) comprising ten analog switches defines how the ATAP and the internal analog bus are (dis)connected, and the six analog switches in each ABM define what connections should be established between the pin, the core circuitry, and the internal analog bus. The large number of analog switches in the 1149.4 test architecture may raise concerns about their integrity, particularly when they are used frequently, as would be the case in an 1149.4-based MS debug strategy. This paper proposes a set of integrity check procedures that address only the 1149.4 extensions: ATAP, TBIC, AB lines, ABMs.